The Implementation of Cambridge Curriculum in Islamic School for English Language Learning: A Systematic Literature Review - Nadia Zahra; Saharudin; Delita Sartika (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to synthesize recent research on how Islamic schools in Indonesia integrate the Cambridge Curriculum into English language learning. In response to growing demands for internationally aligned education, these schools have begun adapting Cambridge-based instruction while maintaining religious and national frameworks. Using the PRISMA approach, eight peer-reviewed empirical studies published between 2022 and 2025 were selected and analyzed thematically. The review finds that Islamic schools generally employ a hybrid model that aligns Cambridge content with national standards and Islamic values. Studies consistently report improvements in students’ English proficiency and classroom engagement. However, recurring challenges appear, including limited teacher preparation, insufficient contextualized materials, and resource constraints. Schools have responded with initiatives such as bridging programs and targeted professional development, though their effectiveness varies. The novelty of this review lies in its specific focus on Cambridge Curriculum implementation within Islamic school settings—a context seldom explored in earlier literature. Rather than detailing every instructional technique, the synthesis highlights broader patterns of adaptation and institutional response. The review suggests that the core issue is not curriculum adoption itself, but how schools interpret and adjust it to fit their pedagogical, cultural, and religious environments.